Gambling and sports in a global age - McGee, Darragh; Bunn, Christopher (Emerald Publishing Limited, 2023)
This volume contains an Open Access chapter. Recent decades have seen an unprecedented expansion and diversification of sports gambling markets. Enabled by widespread access to the internet, advances in smartphone technology and the liberalisation of gambling advertising, gambling companies have strategically invested in the alignment of this practise with culturally embedded sporting activities, leading some to characterise these developments as the 'gamblification' of sports. Bringing together leading scholars from across the world, Gambling and Sports in a Global Age provides a landmark sociological collection on sports gambling from global perspectives. Anchored in a historical sociological context, chapters trace the global transformation of sports gambling amid wider processes of techno-capitalist expansion and the commercialisation of sport before exploring the differential factors that shape the relationship between sport and gambling in unique societal contexts. Contributors examine emerging issues in sports gambling, including the ethics of gambling sponsorship in sport, athlete rights, the risk of harms to youth and the future of sports fandom. Gambling and Sports in a Global Age demonstrates the importance of sociology in understanding sports gambling in a global age, establishing a much-needed scholarly platform with which to generate theoretically informed interventions in research and policymaking. Through an integrated global approach, the contributors shed critical light on centrally relevant sociological themes, providing convenient access to a diverse array of contextual insights and generating new questions for an emerging generation of sociologists.
Includes index.
Keywords: Sports betting -- Sociological aspects.; Internet gambling -- Sociological aspects.; Sports & Recreation -- General.; Sociology: sport & leisure.; elektronické knihy; electronic books